Deletion of mTOR in liver epithelial cells enhances hepatic metastasis of colon cancer. Issue 3 (25th August 2021) - Jiao, Long; Eickhoff, Roman; Egners, Antje; Jumpertz, Sandra; Roth, Johanna; Erdem, Merve; Kroh, Andreas; Duimel, Hans; López‐Iglesias, Carmen; Caro, Pilar; Heij, Lara R; Schmeding, Maximilian; et al.
Abstract: Activation of the mechanistic target of rapamycin (mTOR) pathway is frequently found in cancer, but mTOR inhibitors have thus far failed to demonstrate significant antiproliferative efficacy in the majority of cancer types. Besides cancer cell‐intrinsic resistance mechanisms, it is conceivable that mTOR inhibitors impact on non‐malignant host cells in a manner that ultimately supports resistance of cancer cells. Against this background, we sought to analyze the functional consequences of mTOR inhibition in hepatocytes for the growth of metastatic colon cancer. To this end, we established liver epithelial cell (LEC)‐specific knockout (KO) of mTOR (mTOR LEC ) mice. We used these mice to characterize the growth of colorectal liver metastases with or without partial hepatectomy to model different clinical settings. Although the LEC‐specific loss of mTOR remained without effect on metastasis growth in intact liver, partial liver resection resulted in the formation of larger metastases in mTOR LEC mice compared with wildtype controls. This was accompanied by significantly enhanced inflammatory activity in LEC‐specific mTOR KO livers after partial liver resection. Analysis of NF‐ĸB target gene expression and immunohistochemistry of p65 displayed a significant activation of NF‐ĸB in mTOR LEC mice, suggesting a functional importance of this pathway for the observed inflammatory phenotype. Taken together, we show an unexpected acceleration of liver metastases upon deletion of mTOR in LECs. Our results support the notion that non‐malignant host cells can contribute to resistance against mTOR inhibitors and encourage testing whether anti‐inflammatory drugs are able to improve the efficacy of mTOR inhibitors for cancer therapy. © 2021 The Authors. The Journal of Pathology published by John Wiley & Sons, Ltd. on behalf of The Pathological Society of Great Britain and Ireland.